Monitoring solution in a dynamic Service-Oriented Platform. (October 2017) - Souza, Fabio; Coutinho, Tarcisio; Rosa, Nelson
Highlights: Quality attributes and metrics are fundamental for specifying service compositions. However, there is no consensus on the attributes and metrics that are relevant. An ideal solution should support user-defined attributes and metrics. The paper proposes a meta-model connecting service, quality and event domains. Conformant models are interpreted at runtime to configure service compositions. Graphical abstract: Abstract: Quality attributes play a relevant role in Service-Oriented Computing, as they allow distinguishing similar services. These attributes impact on various activities related to the life-cycle of service-based applications (SBAs). The effect starts from service discovery and permeates other activities such as service level agreement establishment and monitoring. Considering the relevance of quality attributes, they must be precisely defined. Moreover, as these attributes are intrinsically dynamic, they must be permanently monitored. This paper proposes a meta-model that formally defines and connects service, quality and event domains. The connection between service and quality domains enables the design of models that specify applications' functional and non-functional requirements. The connection between quality and event domains allows engineers to define how quality metrics can be computed based on a set of runtime events. Conformant models can be interpreted at runtime by compatible platforms to dynamically configure their monitoring mechanisms.